Kerajinan Manik-Manik dalam Pengembangan Ekonomi Kerakyatan di Kete Kesu Toraja Utara - Pangalo, Nopriani; Nurlela, Nurlela (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the community's efforts in developing bead crafts towards the sustainable economic development of the community in Kete Kesu, North Toraja Regency. To achieve this goal, researchers used data collection techniques through observation, interviews, and documentation. The number of informants in this study were 12 people who had the criteria of bead craftsmen, bead sellers, and local residents. The data obtained from the results of the research were processed using qualitative analysis through three stages, namely data reduction, analyzing data, drawing conclusions or verifying data. The data validation technique uses source triangulation techniques. The results of the study show that (1) The meaning of bead crafts in the Kete Kesu community consists of 7 meanings including: (a) Influencing the economy in Kete (b) Not only as jewelry (c) Not apart from social stratification (d) Not having special meaning but is characteristic of the Toraja people (e) There is a meaning in each color (f) There is a meaning in each motif (g) Requires precision and patience.